Optimal recall period length in consumer payment surveys - Marcin Hitczenko (Federal Reserve Bank of Boston, 2013)
Surveys in many academic fields ask respondents to recall the number of events that occurred over a specific period of time with the goal of learning about the mean frequency of these events among the population. Research has shown that the choice of the recall period, particularly the length, affects the results by influencing the cognitive recall process. We combine experimental recall data with use data to learn about this relationship in the context of consumer payments, specifically for the mean frequency of use of the four most popular payment instruments (cash, credit card, debit card, check).Overall, our analysis suggests that day-based recall is inefficient, with mean-squared errors of population estimates minimized for longer recall periods, although the optimal recall period differs among payment instruments. In addition, for cash, we develop a model relating recalled values to individual frequency of use in order to study the relationship between demographic variables and accuracy at different recall lengths. We find little link between demographic characteristics and accuracy of different recall periods for an individual.
Keywords: C83; 330; consumer payments; stochastic recall models; survey design; mean-squared error; bias